A Novel Endoscopic Treatment of Hemosuccus Pancreaticus: A Stent Tree Tamponade - Gutkin, Ellen; Kim, Sang H (JOP. Journal of the Pancreas, 2012)
Context Hemosuccus pancreaticus is a rare cause of intermittent upper gastrointestinal bleeding, commonly caused by aneurysmal rupture. Prompt diagnosis and treatment is required. The standard treatment involves embolization via interventional radiology or a surgical approach. Case report We report a novel endoscopic approach to hemosuccus pancreaticus with a successful tamponade via pancreatic biliary stents and resolution clips. Conclusion This is the only report of endoscopy as a therapeutic modality in a case of hemosuccus pancreaticus.